2012
DOI: 10.1111/j.1399-3038.2012.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into childhood Vernal keratoconjunctivitis‐associated factors

Abstract: The purpose of this study was to test for detectable serum levels of antibodies usually associated with immune-related diseases in children with Vernal keratoconjunctivitis (VKC) and seek for their family history of allergies and autoimmune disorders. The association of human leukocyte antigens (HLA) with VKC was also investigated. We enrolled 181 VKC children and assessed total and specific IgE, antithyroglobulin (AbTG), antithyroidperoxidase (AbTPO), antitransglutaminase (tTG), and antinuclear antibodies (AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
3
10
0
1
Order By: Relevance
“…However, our study confirms that patients with VKC also present a higher prevalence of thyroid autoimmunity, confirming the findings of Tesse et al [7], who reported a higher rate of positivity of thyroid autoantibodies in patients with VKC compared to healthy subjects, despite the fact that thyroid function in the VKC patients was not studied. The same study also discovered that, in 181 VKC children, 22% were positive for AbTG, 14.6% for AbTPO, and 15.8% for ANA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, our study confirms that patients with VKC also present a higher prevalence of thyroid autoimmunity, confirming the findings of Tesse et al [7], who reported a higher rate of positivity of thyroid autoantibodies in patients with VKC compared to healthy subjects, despite the fact that thyroid function in the VKC patients was not studied. The same study also discovered that, in 181 VKC children, 22% were positive for AbTG, 14.6% for AbTPO, and 15.8% for ANA.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that VKC patients have a significantly higher prevalence of a family history of autoimmune diseases, confirming the data of Zicari et al [6] and Tesse et al [7]. For example, Tesse et al showed that 12.2% of VKC cases had a positive family history of psoriasis; 5.2% of the patient group was positive for thyroiditis, which suggests the role of common components associated with these immune-based diseases in the development of thyroid autoimmunity [7].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14 Recent data have suggested that patients with VKC may have a higher frequency of a family history of autoimmune disorders, antinuclear antibodies and autoimmune thyroid disease. [14][15][16][17] In addition, VKC is more common in the tropics than in northern climates. However, although VKC is a common disorder, particularly in Asia, most Asian patients with AC are diagnosed as having SAC and PAC.…”
Section: Discussionmentioning
confidence: 99%